2022
DOI: 10.3390/ijerph19042375
|View full text |Cite
|
Sign up to set email alerts
|

Stay in Risk Area: Place Attachment, Efficacy Beliefs and Risk Coping

Abstract: For residents living in earthquake-threatened areas, choosing suitable risk coping behaviors can effectively reduce the loss of family life and property. However, some residents still choose to continue to live within areas at risk of earthquake disaster. Place attachment may play an important role. Based on place attachment theory and the Protective Action Decision Model (PADM), this study explores the possible relationships among place attachment, efficacy beliefs, and evacuation/relocation intention. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Studies have shown that involuntary migration can be extremely detrimental to the social stability of the relocated communities [59]. Most residents, living in areas identified as particularly prone to natural disasters, are reluctant to leave their homes [60] because of place attachment [61,62], loverhood, and religion [63][64][65]. Improving the risk perception of natural disasters is an important measure to promote relocation decisions [66].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that involuntary migration can be extremely detrimental to the social stability of the relocated communities [59]. Most residents, living in areas identified as particularly prone to natural disasters, are reluctant to leave their homes [60] because of place attachment [61,62], loverhood, and religion [63][64][65]. Improving the risk perception of natural disasters is an important measure to promote relocation decisions [66].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is difficult to define SPAs universally, as individual differences in cognitions mediate what is meant by SPA. Here, for convenience, we use favoritism toward a region as a proxy indicator of regional attachment.Many previous studies have considered SPA as an independent variable and evaluated its impact on perceived disaster risk and disaster migration intentions (Bonaiuto, Alves et al, 2016;Jansen, 2020;Qing, Guo et al, 2022;Swapan and Sadeque, 2021).In contrast, few previous have analyzed changes in place attachment as a dependent variable related to disaster conditions, other than Ruiz and Herná ndez (2014), who illustrated attenuation of attachment in disaster-stricken areas. Therefore, in this study, we used the example of JP19TP19 in Japan as a working hypothesis to demonstrate increased place attachment.…”
Section: Overall Research Frameworkmentioning
confidence: 99%
“…Even after Hurricanes Katrina and Rita, BP's Macondo Oil well rupture, rising sea level, and the sharp decline in sea-food prices, the main reasons for many residents of Terrebonne Parish, Louisiana, did not leave include the affective bond between people and place, the value these people provide to their cultural capital, and limited resources [83]. Research has shown that residents with strong place attachments were less likely to leave even hazard-prone areas [84][85][86]. In the same way, social resources, such as assistance from caregivers, neighbors, and family in terms of short-term borrowing, remittance, free shelter, and reassurance recovered the affected people, therefore inhibited, to a great extent, outmigration in the aftermath of the severe flood in Kuruwita and Elapatha district, Sri Lanka [87], the 2020 hurricanes in two-semi coastal communities in Mexico (Cohen-Salgado et al 2021), the 2011 Great East Japan Earthquake in 27 coastal cities of Iwate and Miyagi, Japan [88], and the 2009 cyclone Aila [89].…”
Section: Annals Of Social Sciences and Management Studiesmentioning
confidence: 99%